Предсказанные и наблюденные параметры 23-го цикла солнечной активности - Хецуриани, Ц.С.; Гиголашвили, М.Ш.; Ограпишвили, Н.Б. (Известия Крымской астрофизической обсерватории, 2008)
Observational data on changes in the sunspot number and the geomagnetic index are used to forecast the parameters of solar cycle 23. Cycles from 2 to 22 are studied by statistical methods. Our forecast of solar cycle 23 is as follows: the minimum occurs in May 1996, the maximum occurs in June 2000, Wmax = 150 ± 35 (April 2000); the cycle ends in 2007. The minimum and maximum of solar cycle 23 were observed in May 1996 and April 2000, respectively.